(3fTCJg hJWhQg heSJbHdgs - (3ZQjZhQj(B, (3cdGcs; (3Cejf GdCjhHj(B, s ((3HjQhJ(B:s (3GdOGQ GdYQHjI ddYdhe fGTQhf(B,s, 2009)
(3GdeUjOI GdeGdKhSjI GdMjGI GdEbJUGOjI dZGjI GdbQf GdJGSY YTQ(B- (3effWb GdEbJUGO GdeGdKhSj(B- (3eSJhjGJ GdeYjTI(B- (3GdNUhHI(B- (3GdJbOe GdJcfhdhLj(B- (3GdeDSSGJ hGdfeh(B- (3GdKhQI GdUfGYjI(B- (3Gdfeh GdeYGUQ(B- (3GdJHGYO GdcHjQ(B- (3Gdfeh GdYGdej efP (B1800 - (3GdeUGOQ GdeHGTQI ddJHGYO(B- (3deGPG de jJWhQ GdYGde HCcedg? YGde LOjO ZQjHs
Keywords: (3GdEbJUGO GdOhdjs; (3GdEbJUGO GdYGdejs; (3GdJLGQI GdNGQLjIs